2010
DOI: 10.1016/j.pscychresns.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Differential fractional anisotropy abnormalities in adolescents with ADHD or schizophrenia

Abstract: Schizophrenia and ADHD are associated with similar deficits in working memory, attention, and inhibition. Both disorders also involve abnormalities of white matter integrity, possibly reflecting neural communication disruptions. There are likely some regional white matter abnormalities that underlie the common cognitive impairment, though also some regional abnormalities unique to each disorder. We used diffusion tensor imaging (DTI) to compare white matter integrity, as indicated by fractional anisotropy (FA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 40 publications
(50 reference statements)
5
96
3
1
Order By: Relevance
“…This hypothesis is supported by DTI studies (Davenport et al. 2010; van Ewijk et al. 2014) showing uniquely higher FA in ADHD adolescents (compared to adolescents with schizophrenia) in the left and right anterior corona radiata, and higher FA in widespread white matter regions associated with short‐range connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by DTI studies (Davenport et al. 2010; van Ewijk et al. 2014) showing uniquely higher FA in ADHD adolescents (compared to adolescents with schizophrenia) in the left and right anterior corona radiata, and higher FA in widespread white matter regions associated with short‐range connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem studies have shown a genderdiagnosis effect of reduced axonal number (Highley et al, 1999a), oligodendrocyte density loss (Hof et al, 2003), and lower levels of immunoreactivity of oligodendrocyte-associated proteins in the genu of the corpus callosum (Flynn et al, 2003). Diffusion-weighted imaging has been relatively consistent in reporting reduced callosal FA in chronic schizophrenia (Douaud et al, 2007;Koch et al, 2010;Kubicki et al, 2008;Miyata et al, 2010;Mori et al, 2007b;RotarskaJagiela et al, 2008), including during remission (Koch et al, 2010) and less consistently in studies examining individuals at the first episode (Cheung et al, 2008;Gasparotti et al, 2009;Perez-Iglesias et al, 2010b;Peters et al, 2008;Price et al, 2005;Szeszko et al, 2005) or in earlier stages of illness (Davenport et al, 2010;Douaud et al, 2007;Kyriakopoulos and Frangou, 2009). Directly comparing first episode and chronic groups supports more severe changes in FA in the genu of the corpus callosum (Friedman et al, 2008;Kong et al, 2011), the left ILF (Friedman et al, 2008), and ALIC (Bora et al, 2011) in the chronic group including relative to the first episode group.…”
Section: Discussionmentioning
confidence: 99%
“…21,24,25 Our finding of decreased diffusion anisotropy in the left frontostriatal tracts in youths with ADHD is consistent with those of some previous studies using DTI 22,31 and DSI, 21,24 but inconsistent with those of other studies showing increased diffusion anisotropy in children with ADHD. 58,59 Most of the previous studies did not particularly emphasize the difference between the left and right sides of frontostriatal tracts. 22,31 In addition, a previous study from our group reported decreased diffusion anisotropy in the bilateral frontostriatal tracts.…”
Section: Alteration Of White Matter Microstruactual Propertymentioning
confidence: 98%